Ciprofloxacin and Clozapine: A Potentially Fatal but Underappreciated Interaction - Jonathan M. Meyer; George Proctor; Michael A. Cummings; Laura J. Dardashti; Stephen M. Stahl (Case Reports in Psychiatry)
Objective. Clozapine provides a 50%–60% response rate in refractory schizophrenia but has a narrow therapeutic index and is susceptible to pharmacokinetic interactions, particularly with strong inhibitors or inducers of cytochrome P450 (CYP) 1A2. Case Report. We report the case of a 28-year-old nonsmoking female with intellectual disability who was maintained for 3 years on clozapine 100 mg orally twice daily. The patient was treated for presumptive urinary tract infection with ciprofloxacin 500 mg orally twice daily and two days later collapsed and died despite resuscitation efforts. The postmortem femoral clozapine plasma level was dramatically elevated at 2900 ng/mL, and the cause of death was listed as acute clozapine toxicity. Conclusion. Given the potentially fatal pharmacokinetic interaction between clozapine and ciprofloxacin, clinicians are advised to monitor baseline clozapine levels prior to adding strong CYP450 1A2 inhibitors, reduce the clozapine dose by at least two-thirds if adding a 1A2 inhibitor such as ciprofloxacin, check subsequent steady state clozapine levels, and adjust the clozapine dose to maintain levels close to those obtained at baseline.